The impact of food additives, artificial sweeteners and domestic hygiene products on the human gut microbiome and its fibre fermentation capacity. - Gerasimidis, Konstantinos; Bryden, Katie; Chen, Xiufen; Papachristou, Eleftheria; Verney, Anais; Roig, Marine; Hansen, Richard; Nichols, Ben; Papadopoulou, Rodanthi; Parrett, Alison (European Journal of Nutrition, 2020)
Purpose: This study investigated the effect of food additives, artificial sweeteners and domestic hygiene products on the gut microbiome and fibre fermentation capacity. Methods: Faecal samples from 13 healthy volunteers were fermented in batch cultures with food additives (maltodextrin, carboxymethyl cellulose, polysorbate-80, carrageenan-kappa, cinnamaldehyde, sodium benzoate, sodium sulphite, titanium dioxide), sweeteners (aspartame-based sweetener, sucralose, stevia) and domestic hygiene products (toothpaste and dishwashing detergent). Short-chain fatty acid production was measured with gas chromatography. Microbiome composition was characterised with 16S rRNA sequencing and quantitative polymerase chain reaction (qPCR). Results: Acetic acid increased in the presence of maltodextrin and the aspartame-based sweetener and decreased with dishwashing detergent or sodium sulphite. Propionic acid increased with maltodextrin, aspartame-based sweetener, sodium sulphite and polysorbate-80 and butyrate decreased dramatically with cinnamaldehyde and dishwashing detergent. Branched-chain fatty acids decreased with maltodextrin, aspartame-based sweetener, cinnamaldehyde, sodium benzoate and dishwashing detergent. Microbiome Shannon α-diversity increased with stevia and decreased with dishwashing detergent and cinnamaldehyde. Sucralose, cinnamaldehyde, titanium dioxide, polysorbate-80 and dishwashing detergent shifted microbiome community structure; the effects were most profound with dishwashing detergent (R2 = 43.9%, p = 0.008) followed by cinnamaldehyde (R2 = 12.8%, p = 0.016). Addition of dishwashing detergent and cinnamaldehyde increased the abundance of operational taxonomic unit (OTUs) belonging to Escherichia/Shigella and Klebsiella and decreased members of Firmicutes, including OTUs of Faecalibacterium and Subdoligranulum. Addition of sucralose and carrageenan-kappa also increased the abundance of Escherichia/Shigella and sucralose, sodium sulphite and polysorbate-80 did likewise to Bilophila. Polysorbate-80 decreased the abundance of OTUs of Faecalibacterium and Subdoligranulum. Similar effects were observed with the concentration of major bacterial groups using qPCR. In addition, maltodextrin, aspartame-based sweetener and sodium benzoate promoted the growth of Bifidobacterium whereas sodium sulphite, carrageenan-kappa, polysorbate-80 and dishwashing detergent had an inhibitory effect. Conclusions: This study improves understanding of how additives might affect the gut microbiota composition and its fibre metabolic activity with many possible implications for human health.